Efektifitas Aplikasi In-vitro Rizobakteri Sebagai Agen Antagonis Layu Fusarium pada Pisang Rajabulu/AAB di Rumah Kaca - Kasutjianingati .; Roedhy Poerwanto; Widodo .; Nurul Khumaida; Darda Efendi (Jurnal Hortikultura Indonesia, 2011)
Research was conducted on a banana cultivar of Rajabulu/AAB inside the green house. This research was aimed to study the effect of rhizobacteria and the ability of in vitro bacterization to prevent FOC. This study was conducted using split plot design. The main plot was rhizobacteria treatments (P. fluorescens ES-32, B. subtilis SB-3, a mix of both types and without bacteria), sub plots consist of in vitro (2 weeks and 1 week prior to application) and in vivo (during acclimatization) bacterization. All treatments were repeated 3 times, each consist of 7 polibags. The result of rhizobacteria treatment (B. subtilis SB3 or P. fluorecens ES32) was able to reduce the Disease Severity (Rhizome Discoloration) caused by Fusarium oxysporum f.sp cubense (FOC). The incorporation of mixed rhizobacteria provided significant effect suppressing the infestation of FOC. The application of mix bacteria was better than single treatment.Keywords: B. subtilis, P. fluorecens, rhizome discoloration, fusarial wilt, suppressing